Implementation of Teaching Factory in Indonesian Vocational High Schools: A Bibliometric and Systematic Literature Review - Siagian, Maslina; Hantono, Hantono; Haloho, Ronald H.; Arisandy, Dodi; Simaremare, Aman (Indonesian Journal of Advanced Research, 2025)
This study affirms that Teaching Factory (Tefa) is a systemic educational innovation bridging vocational high school learning with industry needs. By embedding authentic production processes into curricula, Tefa supports national economic priorities and global TVET reform principles. Bibliometric analysis identified four clusters: resources and evaluation, competency-based education, operational implementation, and the education–industry–quality link. Publication growth since 2018 reflects strong policy momentum from initiatives such as SMK Revitalization. However, gaps remain in longitudinal employability studies, cost-effectiveness evaluations, and Industry 4.0 integration. Tefa’s success depends on teacher development, curriculum alignment, infrastructure readiness, and industry collaboration. With strategic scaling and continuous improvement, Tefa could serve as a benchmark for vocational education reform in Indonesia and other nations.